A one-carbon chemicals conversion strategy to produce precursor of biofuels with Saccharomyces cerevisiae. (May 2023) - Wang, Kai; Da, Yangyang; Bi, Haoran; Liu, Yanhui; Chen, Biqiang; Wang, Meng; Liu, Zihe; Nielsen, Jens; Tan, Tianwei
Abstract: Utilization of one-carbon chemicals such as CO2, formate, and methanol by microorganisms can enable the sustainable production of fuels and chemicals. However, the low conversion efficiency of these chemicals by microorganisms is a major challenge. To address this, we designed a one-carbon strategy that can utilize CO2 and its derivative formate. Here, a platform yeast strain with improved formate utilization and NAD(P)H production was constructed and evaluated for its ability to produce free fatty acids (FFAs). Based on 13 C-marked analysis, the one-carbon assimilation efficiency of the platform strain reached 11.24%. Through continuous optimization, under conditions of glucose feeding the formate utilization rate of the final strain reached 0.48 g/L/h, with the final titer of FFAs reached 10.1 g/L, which represented improvements of 21.8 times and 33.7 times, respectively. As such, the produced FFAs can be easily transformed into biodiesel by combining them with downstream technologies in future research. Graphical abstract: Image 1